Heterozygous Ldlr-Deficient Hamster as a Model to Evaluate the Efficacy of PCSK9 Antibody in Hyperlipidemia and Atherosclerosis - Wu, Yue; Xu, Ming-Jiang; Cao, Zhiyou; Yang, Chun; Wang, Jinjie; Wang, Bijue; Liu, Jian; Wang, Yuhui; Xian, Xunde; Zhang, Fang; Liu, George; Chen, Xiaoli (International journal of molecular sciences, 2019)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) plays a key role in cholesterol homeostasis and atherogenesis. However, there are only limited rodent models, with a functional low-density lipoprotein receptor (LDLR) pathway and cholesteryl ester transfer protein (CETP) to evaluate the drug candidates targeting the PCSK9/LDLR pathway, that are translatable to humans. Here, by using our recently generated LDLR heterozygote (Ldlr+/−) hamster model with functional LDLR pathway and CETP function, we seek to evaluate the effect of a PCSK9 antibody, evolocumab, on dyslipidemia and atherosclerosis compared with ezetimibe, an effective inhibitor of cholesterol absorption, as a positive therapeutic control. We show that the plasma levels of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) were significantly increased in Ldlr+/− hamsters fed a high-fat high-cholesterol (HFHC) diet; therefore, areas of atherosclerotic lesion in the aorta were obviously increased and positively correlated with plasma LDL-C and TC. Circulating free PCSK9 was downregulated by the HFHC diet and was undetectable in the evolocumab treated group, as expected. Most importantly, either evolocumab or ezetimibe treatment prevented HFHC diet-induced hyperlipidemia and subsequent atherosclerotic plaque formation. The results indicate that Ldlr+/− hamsters fed an HFHC diet represent an ideal rodent model to evaluate drug candidates that affect LDLR pathways.